2021
DOI: 10.3390/molecules26216372
|View full text |Cite
|
Sign up to set email alerts
|

Nano Milk Protein-Mucilage Complexes: Characterization and Anticancer Effect

Abstract: The anticancer activity of natural compounds has recently attracted multidisciplinary research. In this study, the complexation of milk proteins (MP) with Isabgol husk mucilage (IHM) and Ziziphus spina-christi mucilage (NabM) was investigated. In this context, the physicochemical properties of milk protein mucilage complexes (MPMC) including pH, Carr’s index, water solubility, and water absorption indices were measured, and the flow behavior was studied. In addition, the amino acid profile, protein digestibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…To eliminate this possibility, a viable idea is to decipher the active region in SEM-Mb responsible for anti-leukemia activity and then use this active region to develop peptidomimetics. Notably, El-Maksound et al [65] reported that milk protein-mucilage complexes formed by milk proteins with Isabgol husk mucilage or Ziziplus spina-christi mucilage enhanced the anti-cancer activity of milk proteins. As reducing the dose and frequency of using SEM-Mb can delay its potential antibody induction, complexation of SEM-Mb with natural components may be a feasible strategy to increase its anti-leukemia activity at a reduced dose.…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate this possibility, a viable idea is to decipher the active region in SEM-Mb responsible for anti-leukemia activity and then use this active region to develop peptidomimetics. Notably, El-Maksound et al [65] reported that milk protein-mucilage complexes formed by milk proteins with Isabgol husk mucilage or Ziziplus spina-christi mucilage enhanced the anti-cancer activity of milk proteins. As reducing the dose and frequency of using SEM-Mb can delay its potential antibody induction, complexation of SEM-Mb with natural components may be a feasible strategy to increase its anti-leukemia activity at a reduced dose.…”
Section: Discussionmentioning
confidence: 99%